1999
DOI: 10.3168/jds.s0022-0302(99)75210-0
|View full text |Cite
|
Sign up to set email alerts
|

Competition for Total Mixed Diets Fed for Ad Libitum Intake Using One or Four Cows per Feeding Station

Abstract: When dairy cow facilities are being designed, a limited feeding area might be profitable and recommendable if the increased competition for feed does not harm the welfare of the animals or affect production negatively. An experiment was conducted at the University Cattle Research Centre (Uppsala, Sweden) to investigate the performance of individual cows as well as groups of cows. Treatments used 1 or 4 cows per feeding station with a total mixed diet fed for ad libitum intake. The feeding stations were troughs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
100
5
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 9 publications
16
100
5
4
Order By: Relevance
“…Rice straw as roughage source was restricted to 1 kg DM/d and offered prior to concentrates feeding during the feedlot period hence there was no refusal of rice straw regardless of treatment types. The results of total DMI in our study were in agreement with those of Gonyou and Stricklin (1998), whereas others found slight differences in feed intake in relation to stocking density (Huzzey et al, 2006;McConnell et al, 1987;Olofsson, 1999).…”
Section: Effect Of Stocking Density On Feed Intakesupporting
confidence: 82%
“…Rice straw as roughage source was restricted to 1 kg DM/d and offered prior to concentrates feeding during the feedlot period hence there was no refusal of rice straw regardless of treatment types. The results of total DMI in our study were in agreement with those of Gonyou and Stricklin (1998), whereas others found slight differences in feed intake in relation to stocking density (Huzzey et al, 2006;McConnell et al, 1987;Olofsson, 1999).…”
Section: Effect Of Stocking Density On Feed Intakesupporting
confidence: 82%
“…Dominant cows tend to spend more time eating in a competitive situation than cows with a lower social rank, if feeder space is restricted (ALBRIGHT 1993). In a competition situation, cows consume more feed but spend less time per day for feed intake (OLOFSSON 1999). In the current study, the ratio of 2 cows per feeder might lead to a competitive situation, which can affect feeding behaviour characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Even with unlimited access to feed, cattle interact in ways that may give some individuals an advantage over others in the group (Olofsson, 1999). When a competitive situation exists at the feedbunk, dominant cows typically spend more total time eating than cows of lower social rank, resulting in greater DMI.…”
Section: Grouping Social Dominance and Competition For Feedmentioning
confidence: 99%